Efecto en el ambiente y salud de la población de Iquitos por trabajos de alcantarillado de empresa China CWE 2021 - Lozano Bazan, Jampier Arles (2023)
The work was developed in Iquitos, with the purpose of determining the existent association between the effect in the atmosphere and the population's health, generated during the works carried out by company China-CWE, with the increment of noises, contamination of water, contamination of the air, breathing, ophthalmic and gastrointestinal infections, the population was conformed by the residents of the avenues (1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16 and 17 Admiral Grau). The work corresponds to the -inductive logical type of complete type, the design was descriptive and explanatory, establishing the relationship degree between the effects of the atmosphere and the population's health, being reached the conclusion: The execution of the sewer system works executed by the company China CWE, had and it continues having until the present time, a negative direct effect in the population in study (100%). The effect was direct in the Environmental part (100%) and in the population's Health (77.4), due to the excavations, gutters left outdoors, adult increased especially of insect of flies and wading (100%), powder presence (100%) and constant noises for you scheme them (92%), contamination of the air (100%), increment of breathing illnesses (46.7%), ophthalmic (30.7%), gastrointestinal (15.3%), etc. Until the present time, this work continues and it will continue having negative effect for its bad execution and, this is observed especially in time of more pluvial precipitation in the city (100%).